BESARNYA RAHMAT ALLAH SWT DALAM Q.S. AZZUMAR (39) : 53 - Frezzi Ramadhan Syah; Habibie Ramadhan (Student Research Journal, 2023)
Enjoyment and all forms of human sustenance are blessings and favors that Allah has given, every effort that humans have made is an offering from Allah SWT. Long before humans are born, until they live life on earth, and until humans die, humans are never separated from the grace and favor of Allah SWT. Research written using descriptive qualitative methods and writing that uses research methods that use literature study which uses primary sources and scientific secondary sources such as ebooks, articles, and other sources of information. By using the meaning of QS. AzZumar: 53 which explains the greatness of the grace and blessings that Allah has given to humans, so understanding the meaning of this verse will give humans motivation to be grateful for all His blessings. So it can be concluded that this research will explain the form of Allah's grace and blessings extraordinary and how to be grateful for these blessings in the perspective of QS. Az-Zumar; 53.In God's grace free from any danger whatsoever. Because every grace must bring goodness and benefit. If there is a Muslim who is able to do good perfectly in worshiping Allah and is 'qualified' in providing benefits for His other servants, then for him a large portion is in the form of mercy from Allah.